Silence of a dependence receptor CSF1R in colorectal cancer cells activates tumor-associated macrophages - Rui Ma; Ping Yuan; Xiaolin Wang; Yingjie Li; Meijin Huang; Huichuan Yu; Yanxin Luo; Mingxuan Zhu; Liangliang Bai; Xiaoxia Liu; Shaoyong Peng; Yumo Xie; et al. (Journal for ImmunoTherapy of Cancer)
Background Colony-stimulating factor 1 receptor (CSF1R), a classic tyrosine kinase receptor, has been identified as a proto-oncogene in multiple cancers. The CSF1/CSF1R axis is essential for the survival and differentiation of M2-phenotype tumor-associated macrophages (M2 TAMs). However, we found here that the CSF1R expression was abnormally down-regulated in colorectal cancer (CRC), and its biological functions and underlying mechanisms have become elusive in CRC progression.Methods The expression of class III receptor tyrosine kinases in CRC and normal intestinal mucosa was accessed using The Cancer Genome Atlas and Gene Expression Omnibus datasets and was further validated by our tested cohort. CSF1R was reconstructed in CRC cells to identify its biological functions in vitro and in vivo. We compared CSF1R expression and methylation differences between CRC cells and macrophages. Furthermore, a co-culture system was used to mimic a competitive mechanism between CSF1R-overexpressed CRC cells and M2-like macrophages. We utilized a CSF1R inhibitor PLX3397 to ablate M2 TAMs and evaluated its efficacy on CRC treatment in animal models.Results We found here that the CSF1R is silenced in CRC, and the reintroduced expression of the receptor in CRC cells can be cleaved by caspases and constrain tumor growth in vitro and in vivo, functioning as a tumor suppressor gene. We further identified CSF1R as a novel dependence receptor, which has the potential to act as either a tumor suppressor gene or an oncogene, depending on its activated state. In CRC tumors, CSF1R expression is enriched in TAMs, and its expression is associated with poor prognosis in patients ith CRC. In a co-culture system, CRC cells expressing CSF1R compete with M2-like macrophages for CSF1R ligands, resulting in a decrease in CSF1R activation and cell proliferation in macrophages. Blocking CSF1R by PLX3397 could deplete M2 TAMs and augments CD8+ T cell infiltration, effectively inhibiting tumor growth and metastasis and improving responses to chemotherapy and immunotherapy.Conclusion Our findings revealed that CSF1R is a novel identified dependence receptor silenced in CRC. The silence abalienates its ligands to stimulate CSF1R expressed on M2 TAMs, which is an appealing therapeutic target for M2 TAM depletion and CRC treatment.